FORMATION AND DEVELOPMENT OF INNOVATIVE COTTON-TEXTILE CLUSTER IN KAZAKHSTAN - Vilena Seitova; Roland Giese (Academic Journal of Physical and Chemical Sciences, 2019)
The article is devoted to the formation and development of innovative services in the cotton industry. Innovation is an objective stimulus and a prerequisite for the dynamic development of the economy. A comparative analysis of the new innovative cotton variety “Turkistan” was carried out, the possibilities of their introduction in production were investigated. The introduction of innovation results, first of all, will contribute to the sustainable economic growth of the cotton industry and, secondly, increase the competitiveness of cotton-textile cluster production in the country. Innovative cluster approach allows to mobilize all economic factors in the certain direction. Cluster development today is a widely recognized instrument that provides economic development and competitiveness. Rapid growth of cluster initiatives in developed and developing countries has shown their effectiveness and viability. The usage of the cluster model in the development of cotton-textile industry in Kazakhstan is a key factor in the competitiveness of the private companies and the economy associated with the production.